2020
DOI: 10.3390/ani10101819
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age at Weaning and Length of Lipid Supplementation on Growth, Metabolites, and Marbling of Young Steers

Abstract: The objective of this study was to determine how weaning age, days on supplements, and lipid supplementation affected the growth and marbling deposition of steers. Steers from a single sire were early weaned (n = 24) at 150 ± 11 days of age or traditionally weaned (n = 24) at 210 ± 11 days of age. Steers were assigned to control (n = 12/weaning group) or an isocaloric, isonitrogenous rumen by-pass lipid (RBL, n = 12/weaning group) for either 45 (n = 6/treatment) or 90 (n=6/treatment) days then harvested. Steer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Hence, these authors concluded that CSSO supplementation to EW steers enhanced early adipocyte hyperplasia and differentiation (Mangrum et al, 2016). Accordingly, Tipton et al (2020) also reported increased adipocyte hyperplasia in intramuscular adipose tissue of EW steers supplemented with CSSO for 90 days, evidenced by decreased adipocyte diameter. The same result was not evident in traditionally weaned steers provided the same supplementation, indicating that providing CSSO supplementation earlier in life may result in a greater number of undifferentiated stem cells driven toward adipogenic confirmation and differentiation (Tipton et al, 2020).…”
Section: Metabolic Imprinting In Early-weaned Beef Calvesmentioning
confidence: 90%
“…Hence, these authors concluded that CSSO supplementation to EW steers enhanced early adipocyte hyperplasia and differentiation (Mangrum et al, 2016). Accordingly, Tipton et al (2020) also reported increased adipocyte hyperplasia in intramuscular adipose tissue of EW steers supplemented with CSSO for 90 days, evidenced by decreased adipocyte diameter. The same result was not evident in traditionally weaned steers provided the same supplementation, indicating that providing CSSO supplementation earlier in life may result in a greater number of undifferentiated stem cells driven toward adipogenic confirmation and differentiation (Tipton et al, 2020).…”
Section: Metabolic Imprinting In Early-weaned Beef Calvesmentioning
confidence: 90%
“…Serum was then collected into separate tubes and stored at −20 °C until analysis. Duplicate 1 mL serum aliquots from all steers were lyophilized (HarvestRight, North Salt Lake, UT, USA) and then transmethylated according to Tipton et al [ 19 ]. An internal standard, methyl tricosanoic (C23:0), was incorporated into each sample during methylation.…”
Section: Methodsmentioning
confidence: 99%
“…It is currently believed that early weaning, especially when combined with supplemental feeding, can enhance IMF deposition. Tipton and colleagues found that early weaning at around 150 days of age combined with isonitrogenous rumen bypass lipid supplementation significantly increased the IMF content in Angus steers, without negatively affecting the dressing percentage, when compared to traditional weaning at around 210 days of age [ 87 ]. Angus–Wagyu crossbred heifers subjected to early weaning (142 days of age) and a high-concentrate diet showed greater IMF deposition and weight gain compared to heifers weaned at 180 days and grown on pasture for 16 months before entering the feedlot [ 88 ].…”
Section: Factors That Determine Intramuscular Fat Development and Gro...mentioning
confidence: 99%